Development of soil characteristics database system for Kuantan area - Surain, Sazali (2012)
One of the vital works before a construction begin was a site investigation which was the site exploration to gain the result for the soil characteristics at the construction area. By undergo some necessary required test such as deep borehole logs, water level measurement, JKR Probe, standard penetration test (SPT) and others, the engineers able to design a suitable, safety and economic structures for the building. Usually, the report for the site investigation was in a hard copy and it required a lot of papers for one site investigation report. Other than that, it hard to retrieve the data for site investigation report from all places in one time because of the data was in different hard copy. To solve this matter, a database system for soil characteristic was developed to make all the site investigation data report easily to retrieve in one time and able to be updated from time to time if there was any new result obtained. This database system was developed for Kuantan area only. There were 16 site investigation report data was successfully collected and had been placed in one database system. The tools that had been used to develop this database system were Geographical Information System (GIS) and Visual basic 6.0 (VB6.0). GIS tool was used to provide the map for Kuantan areas. Meanwhile, VB6.0 was used to make the interface design and created the database system for the site investigation data report. To ensure that the map from GIS tools were able to relate with the database system from VB6.0, a hyperlink was created. So, by selecting the site investigation point from the map in GIS, the result of the site investigation appeared easily without used much time. Lastly, this database system would be one of the necessary database systems in construction field because of it availability to retrieve data easily and all the site investigation data was placed in one database system.